2002
DOI: 10.1038/ncb884
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced G2–M checkpoint activation by histone H2AX and 53BP1

Abstract: Activation of the ataxia telangiectasia mutated (ATM) kinase triggers diverse cellular responses to ionizing radiation (IR), including the initiation of cell cycle checkpoints. Histone H2AX, p53 binding-protein 1 (53BP1) and Chk2 are targets of ATM-mediated phosphorylation, but little is known about their roles in signalling the presence of DNA damage. Here, we show that mice lacking either H2AX or 53BP1, but not Chk2, manifest a G2-M checkpoint defect close to that observed in ATM(-/-) cells after exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
505
1
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(540 citation statements)
references
References 25 publications
26
505
1
8
Order By: Relevance
“…Although Chk2 is phosphorylated by ATM in response to DSBs, we and others have observed that Chk2-deficient cells effect G2/M checkpoint arrest proficiently after IR (although they have been reported in other studies to be defective in the maintenance of this arrest) [27,28](Deckbar, manuscript submitted) . The failure of Chk2-deficient cells to arrest is most likely due to overlapping functions of Chk1 and Chk2 [29].…”
Section: Apoptosismentioning
confidence: 70%
“…Although Chk2 is phosphorylated by ATM in response to DSBs, we and others have observed that Chk2-deficient cells effect G2/M checkpoint arrest proficiently after IR (although they have been reported in other studies to be defective in the maintenance of this arrest) [27,28](Deckbar, manuscript submitted) . The failure of Chk2-deficient cells to arrest is most likely due to overlapping functions of Chk1 and Chk2 [29].…”
Section: Apoptosismentioning
confidence: 70%
“…Based on its very early appearance, it was assumed that g-H2A.X is a very early response to DSBs and, hence, required for the recruitment of DSB signaling and repair proteins to the sites of DSBs. This hypothesis was supported by data showing that the accumulation in DSB repair foci of numerous repair proteins including 53BP1, BRCA1, and MDC1 is impaired in H2A.X null cells [Bassing et al, 2002;Celeste et al, 2002;Fernandez-Capetillo et al, 2002;Stewart et al, 2003]. In contrast, another study from the Nussenzweig lab showed that H2A.X is dispensable for the initial recruitment of these proteins to the sites of DSBs in MEFs lacking H2A.X expression [Celeste et al, 2003b].…”
Section: C-h2ax and The Dsb Responsementioning
confidence: 90%
“…In concordance with these data, recent studies showed that many proteins that are involved in DNA repair and that are activated by ATM/ATR are overexpressed in the nuclei of senescent cells and form DNA damage foci at dysfunctional telomeres (8,54) and intragenomic double-strand breaks (45). These proteins include phosphorylated H2AX (␥-H2AX), a common marker of cellular double-strand breaks that in turn promotes the assembly of several checkpoint and DNA repair factors (e.g., 53BP1, MDC1, and NBS1) at the site of DNA damage (17,52). To explore whether the dysfunctional telomeres and doublestrand breaks in senescent cells elicit a constitutive DNA damage signal irrespective of external factors, the localization and expression of these proteins (␥-H2AX, 53BP1, MDC1, and NBS1) in early-and late-passage HK1 cells under serial passage, serum starvation, and serum restimulation were monitored.…”
Section: Resultsmentioning
confidence: 99%